2008
DOI: 10.1038/sj.bjc.6604660
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of protein tyrosine kinase 6 (PTK6) for long-term survival of breast cancer patients

Abstract: The cytoplasmic tyrosine kinase PTK6 (BRK) shows elevated expression in approximately two-thirds of primary breast tumours, and is implicated in EGF receptor-dependent signalling and epithelial tumorigenesis. Using immunohistochemistry, we performed a retrospective study on 426 archival breast cancer samples from patients with long-term follow-up and compared the protein expression levels of PTK6, the HER receptors, Sam68 (a substrate of PTK6), and signalling proteins including MAP kinase (MAPK), phosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 35 publications
(81 reference statements)
1
60
0
Order By: Relevance
“…PTK6 was also shown to be expressed in several cancer cell lines (11)(12)(13). In the last decade, we and others have identified several interaction partners of PTK6, such as STAT3, (p38) MAPK, Paxillin, and PTEN (14)(15)(16)(17). Therefore, PTK6 seems to be involved in several cellular processes, such as proliferation, migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTK6 was also shown to be expressed in several cancer cell lines (11)(12)(13). In the last decade, we and others have identified several interaction partners of PTK6, such as STAT3, (p38) MAPK, Paxillin, and PTEN (14)(15)(16)(17). Therefore, PTK6 seems to be involved in several cellular processes, such as proliferation, migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the HER2 and PTK6 mRNA and protein levels are positively correlated, emphasizing their role as crucial molecules in breast cancer (17,(20)(21)(22). In 2004, Tanner and colleagues identified a novel HER2-overexpressing cell line that is intrinsically resistant to trastuzumab and named it JIMT-1 (23).…”
Section: Introductionmentioning
confidence: 99%
“…Coexpression of Brk and HER2 has been linked to co-amplification of both the ErbB2 and ptk6 genes [35] , although this is not a consistent finding in other patient studies. It is worth noting that although HER2 is over expressed in 20%-30% of breast cancers [44] , Brk is over expressed in upto 86% of breast cancers [47] , which indicates that in the majority of breast cancers Brk is over expressed independently of HER2 status.…”
Section: Examples Of Tyrosine Kinase Inhibitors In Breast Cancer-lapamentioning
confidence: 99%
“…Without cellular targeting via an NLS or myristoylation, Brk's cellular localization is not tightly regulated; as a result, we now know that it can be found localized in different cellular compartments based on its protein-protein interactions. It has been reported at the membrane via association with ErbB growth factor receptors and the adamalysin ADAM15 (Zhong et al, 2008), in the cytoplasm interacting with paxillin and mitogen activated protein (MAP) kinase (Aubele et al, 2008;Chen et al, 2004) as well as in the nucleus through interactions with RNA binding proteins such as Src-associated in mitosis-68 (Sam68) and the Sam68-like mammalian proteins, SLM1 and SLM2 (Derry et al, 2000;Haegebarth et al, 2004). In normal human prostate epithelial cells and welldifferentiated prostate carcinomas, Brk was localized in the nucleus whereas poorly differentiated prostate tumours had cytoplasmic Brk (Derry et al, 2003).…”
Section: Brk Localizationmentioning
confidence: 99%
“…For example, the importance of ErbB signalling in breast tumour progression has been well-documented (reviewed in Navolanic et al, 2003) and clinical inhibition of this pathway with therapies such as trastuzumab and lapatinib is now routine for relevant sub-types of breast cancer (CRUK website). Brk associates with all 4 members of the ErbB receptor family (Aubele et al, 2008;Kamalati et al, 1996; and therefore is capable of promoting downstream signalling in response to ErbB ligand binding. Brk also attenuates EGFR signalling through interaction with and phosphorylation of ARAP1 (also known as Arf-GAP, Rho-GAP, ankyrin repeat, and pleckstrin homology (PH) domaincontaining protein 1) (Kang et al, 2010), as well as regulating possibly regulating signalling via reported interactions with PTEN and Akt (Aubele et al, 2008;Zhang et al, 2005).…”
Section: Substrates and Interacting Proteinsmentioning
confidence: 99%